2020
DOI: 10.1021/acs.joc.9b03302
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric [4 + 2] Cycloaddition of ortho-Alkenyl Naphthols/Phenols with ortho-Quinone Methides: Highly Stereoselective Synthesis of Chiral 2,3,4-Trisubstituted Chromans

Abstract: Chiral phosphoric acid-catalyzed biomimetic asymmetric [4 + 2] cycloaddition of ortho-alkenyl naphthols/phenols and ortho-quinone methides (o-QMs) has been demonstrated to afford various important 2,3,4-trisubstituted chromans in high yields with excellent enantio-and diastereoselectivities (up to 99% yield, 99% ee, >20:1 dr). Notably, this methodology not only enabled access to the trans−cis chiral trisubstituted chromans from 1-alkenyl 2-naphthols but also is compatible with 2-alkenyl 1naphthols and phenols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 79 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Scheme 3 [4+2]-Cycloaddition of ortho-benzyl alcohols 1 with 2-vinyl indoles 5, 1-styrenyl-2-naphthols 7, simple styrenes 9 and vinyl sulfides 11. [5][6][7][8][9][10][11] Quite interestingly, the Rueping studies revealed that monoactivation of the o-QM with no binding of the chiral Brønsted acid to the dienophile could result in a highly enantioselective cycloaddition reaction as well. 5 Thus, simple styrenes delivered chromane products with excellent enantioand diastereoselectivity with a phosphoramide catalyst.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 3 [4+2]-Cycloaddition of ortho-benzyl alcohols 1 with 2-vinyl indoles 5, 1-styrenyl-2-naphthols 7, simple styrenes 9 and vinyl sulfides 11. [5][6][7][8][9][10][11] Quite interestingly, the Rueping studies revealed that monoactivation of the o-QM with no binding of the chiral Brønsted acid to the dienophile could result in a highly enantioselective cycloaddition reaction as well. 5 Thus, simple styrenes delivered chromane products with excellent enantioand diastereoselectivity with a phosphoramide catalyst.…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…Scheme 3 [4+2]-Cycloaddition of ortho-benzyl alcohols 1 with 2-vinyl indoles 5, 1-styrenyl-2-naphthols 7, simple styrenes 9 and vinyl sulfides 11[5][6][7][8][9][10][11] …”
mentioning
confidence: 99%
“…Therefore, this reaction system involving o-hydroxynaphthalene needed to continue to optimize the reaction conditions. Subsequently, other groups including Zhang [20] (Scheme 8a), Yuan and You [21] (Scheme 8b), Deng and Shao [22] (Schemes 8c and 8d) independently published beautiful works about the same cycloaddition process of o-hydroxynaphthalene 34 by using different CPA catalysts, again forming a wide range of polysubstituted chromans (35,40) with high level of stereoselectivities. Notably, the lessexplored ortho-alkenyl 1-naphthols were also compatible in this methodology to deliver trans-trans chiral trisubstituted chromans 40.…”
Section: Chiral Phosphoric Acidmentioning
confidence: 99%
“…On the other hand, SPINOL-derived F6 delivered trans-trans configured products 162' (Scheme 30). 37 Scheme 30 Chiral phosphoric acids in diastereodivergent reactions developed by Deng and Shao et al In 2015, Schneider and co-workers documented [4+2] annulation between in situ generated o-QMs and enamides directing to an efficient synthesis of tetrahydroxanthenes bearing three contiguous stereocenters. In this formal Diels-Alder reaction, chiral phosphoric acid F7 was employed as the catalyst which activates o-QMs through hydrogen-bonding (TS20), and facilitates conjugate addition and cyclization sequence to furnish the chiral products 164. ortho-Hydroxyl benzylalcohol 156 were used as the o-QM precursor and the variation in both aryl groups (Ar 1 and Ar 2 ) were well suited for this reaction.…”
Section: Brønsted Acidsmentioning
confidence: 99%